Sirolimus therapy in a child with partially diazoxide-responsive hyperinsulinaemic hypoglycaemia. (25th October 2016) - Loke, Kah-Yin; Anjian, Andrew Sng; Yijuan, Yvonne Lim; Ho Wei Li, Cindy; Güemes, Maria; Hussain, Khalid
Summary: Hyperinsulinaemic hypoglycaemia (HH), which causes persistent neonatal hypoglycaemia, can result in neurological damage and it's management is challenging. Diazoxide is the first-line treatment, albeit not all patients will fully respond to it, as episodes of hypoglycaemia may persist and it entails unpleasant adverse effects. Sirolimus, an mTOR inhibitor, has reportedly been successful in treating children with severe diffuse HH, thus obviating the need for pancreatectomy. We report a girl with HH, with a novel heterozygous ABCC8 gene missense mutation (c.4154A>T/ p.Lys1385Thr), who was initially responsive to diazoxide therapy. After 11 months of diazoxide treatment, she developed intermittent, unpredictable breakthrough episodes of hypoglycaemia, in addition to generalized hypertrichosis and weight gain from enforced feeding to avoid hypoglycaemia. Sirolimus, which was commenced at 15 months of age, gradually replaced diazoxide, with significant reduction and abolition of hypoglycaemia. The hypertrichosis resolved and there was less weight gain given the reduced need for enforced feeding. Sirolimus, which was administered over the next 15 months, was well tolerated with no significant side effects and was gradually weaned off. After stopping sirolimus, apart from hypoglycaemia developing during an episode of severe viral gastroenteritis, the capillary glucose concentrations were maintained >3.5 mmol/L, even after a 10 h fast. Sirolimus may have a role in the treatment of partially diazoxide-responsive forms of HH who experience breakthrough hypoglycaemia, but the long-term safety and efficacy of sirolimus are not established. Learning points: Conventional treatment of diffuse HH with diazoxide is not always effective in controlling hypoglycaemia and can be associated with unpleasant side effects. Sirolimus was successfully used to abolish recurrent hypoglycaemia in partially diazoxide-responsive HH, with resolution of unacceptable diazoxide-associated side effects. Sirolimus was well tolerated with no clinically significant side effects. Shortly after stopping sirolimus, the capillary glucose levels remained normoglycemic.